Zinc Sulphate and Boron-Based Foliar Fertilizer Effect on Growth, Yield, Minerals, and Heavy Metal Composition of Groundnut (Arachis hypogaea L) Grown on an Alfisol - Christopher Aboyeji; Oluwagbenga Dunsin; Aruna O. Adekiya; Chinomnso Chinedum; Khadijat O. Suleiman; Faith O. Okunlola; Charity O. Aremu; Iyiola O. Owolabi; Temidayo A. J. Olofintoye (International Journal of Agronomy)
Field experiments were conducted during 2016 and 2017 cropping seasons in the derived agro-ecological zone of Nigeria to study the combined and sole effect of zinc and boron fertilizers on the growth, seed yield, and quality of groundnut (Arachis hypogaea L). The experiment was laid out in randomized complete block design (RCBD), replicated four times. Three levels of zinc (0, 4, and 8 kg·ha−1) and four levels of boron (0, 300, 600, and 900 ml·ha−1) were combined and evaluated. Groundnut seeds were analyzed at the end of the experiments to determine nutrient elements and some heavy metal contents. Data collected were subjected to Statistical Analysis of Variance using SAS 2000. Treatment means were compared using the Duncan multiple range test at 0.05 level of probability. The effect of zinc was not significant on the vegetative parameters, while application 8 kg Zn·ha−1 significantly increased number of seeds, weight of seeds, seed yield per hectare, and seed quality though the values were similar to the application of 4 kg Zn·ha−1 only on the seed yield and its parameters. Application of 600 and 900 ml B·ha−1 gave higher and statistically similar values for vegetative parameters, yield, and yield parameters, while 600 ml B·ha−1 significantly improved the seed quality. It can therefore be recommended that for optimum yield and seed quality, application of 8 kg Zn·ha−1 combined 600 ml B·ha−1 is sufficient in the study area without increasing the heavy metal concentration of groundnut seed.